2022
DOI: 10.1071/rd22020
|View full text |Cite
|
Sign up to set email alerts
|

-Acetylcysteine improves oocyte quality through modulating the Nrf2 signaling pathway to ameliorate oxidative stress caused by repeated controlled ovarian hyperstimulation

Abstract: Context N-acetyl-cysteine (NAC) is a potent antioxidant that can be used for many gynecological diseases such as polycystic ovary syndrome and endometriosis. Controlled ovarian hyperstimulation (COH) is a critical step in infertility treatment. Our previous clinical studies have shown that repeated COH led to oxidative stress in follicle fluid and ovarian granulosa cells. Aims In this study, we investigated whether NAC could inhibit oxidative stress in mice caused by repeated COH and improve the mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…In addition, NAC improves mitochondrial function and promotes the nuclear translocation of nuclear factor erythroid 2‐related factor 2 that enhances the expression of the antioxidant enzymes SOD and GSH peroxidase (Fan et al. 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NAC improves mitochondrial function and promotes the nuclear translocation of nuclear factor erythroid 2‐related factor 2 that enhances the expression of the antioxidant enzymes SOD and GSH peroxidase (Fan et al. 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the mucolytic and fluidifying effect can improve both the quality of cervical mucus, facilitating the ascent of spermatozoa through the female genital tracts, and the tubal function in patient fallopian tubes [ 32 ], detectable by using the sonohysterosalpingography [ 33 ]. Recently, a study conducted by Fan et al demonstrated how NAC, in vitro, reduces mitochondrial damage in oocytes [ 34 ]. Finally, the reduction of painful symptoms allowed an increased rate of sexual intercourses, with a higher probability of conception.…”
Section: Discussionmentioning
confidence: 99%
“…It also possesses direct antioxidative activities thanks to the disulfide bond reduction and ROS scavenging capacity of its thiol group. NAC has been shown to modulate the Nrf2 pathway, either indirectly by ROS quenching‐mediated Nrf2 activity rescue, 165 by increasing Nrf2 expression, 166–168 or more directly by promoting the nuclear translocation of Nrf2 169 . NAC is a cosmetic ingredient (as an AOX and skin conditioner 117 ) and its potential use in dermatology has been recently reviewed, however, no direct link has been made with Nrf2 pathway induction 170 .…”
Section: Research Strategy For Nrf2 Modulators In Skin and Scalp Carementioning
confidence: 99%
“…NAC has been shown to modulate the Nrf2 pathway, either indirectly by ROS quenching-mediated Nrf2 activity rescue, 165 by increasing Nrf2 expression, [166][167][168] or more directly by promoting the nuclear translocation of Nrf2. 169 NAC is a cosmetic ingredient (as an AOX and skin conditioner 117 ) and its potential use in dermatology has been recently reviewed, however, no direct link has been made with Nrf2 pathway induction. 170 Indeed, NAC may act via several mechanisms not fully described yet.…”
Section: Polyphenolsmentioning
confidence: 99%